The Argumentative Trilogy: Ethos, Pathos, logos Looking into How into Persuade - Aida HAMIMID (Revue des Sciences Humaines, 2015)
Persuasive/Argumentative writing is an important and a difficult mode of discourse. It is mainly difficult for non-native speakers who often bring linguistic and rhetorical scantiness to the task of persuasion in English. Although persuasion in oral and written discourse has been widely studied by rhetoricians and philosophers, we wish, through our research to shed some light on how to improve teaching and learning argumentative writing through a genre approach. We evenly wish to investigate ways to teach and allow our students learn how to appropriately use rhetoric in their writing using political discourse as a model.